Elaborative feedback and instruction improve cognitive reflection but do not transfer to related tasks. (3rd April 2023) - Calvillo, Dustin P.; Bratton, Jonathan; Velazquez, Victoria; Smelter, Thomas J.; Crum, Danielle
Abstract: Cognitive reflection, or the ability to inhibit intuitive and incorrect responses in favour of correct responses, predicts performance on a variety of cognitive tasks. The present study examined interventions to improve cognitive reflection. In two experiments, college students ( N = 491) were assigned to one of three conditions, completed two versions of a cognitive reflection test (CRT), and then completed transfer tasks. Between the two CRTs, some participants were provided with elaborative feedback, others were instructed to consider additional responses for their initial responses and the final group was a control. In both experiments, CRT performance increased between the first and second CRT in the feedback and instruction groups, but not in the control group. There was little evidence, however, for transfer to other tasks. These results suggest that cognitive reflection performance can be improved with brief interventions but that this improvement may not transfer to related tasks.